Factors Affecting Audit Going Concern Opinion and the Role of Supply chain strategy: Evidence from Banking Company in Indonesia - Jatmiko, Bambang; Ladiva, Siti; Machmuddah, Zaky; Suhana, Suhana; Laras, Titi (ExcelingTech, 2020)
The purpose of this study was to determine the effect of financial condition, auditor's reputation, disclosure of financial statements, audit opinion of the previous year, supply chain strategy on going concern audit opinion. Sampling in this study was obtained using a purposive sampling method by focusing on banking companies listed on the Indonesia Stock Exchange in the 2015-2018 period, so that a sample of 24 companies was obtained with 96 observations. The data analysis method used in this study was Warp PLS version 5.0. Based on the results of the analysis it is known that the variables of financial condition, auditor's reputation, disclosure of financial statements, and audit opinions of the previous year affect the going concern audit opinion. In addition, the supply chain strategy moderates the auditor's reputation for going concern audit opinion. The implication of this research is that investors are required to pay attention to negative signals when investing related to the sustainability of the company's life or in other words an early warning for investment decisions.